DETERMINANTS OF SOCIAL ENTREPRENEURSHIP FROM ISLAMIC PERSPECTIVE - Rosihaza, Yosa Sabarina; Admeinasthi, Mutiara Baby; Gandakusuma, Imo; Daryanti, Sri; Kasari Sulung, Liyu Adhi (I-iECONS e-proceedings, 2023)
Along with the increasing Muslim population in Indonesia, the greater opportunity to develop Islamic social entrepreneurship. This research was conducted to find out the factors that influence the intention of Islamic social entrepreneurship in Indonesian Muslim communities through observing the effect of prior experience, empathy, moral obligation, self-efficacy, and perceived social support on social entrepreneurial intentions based on Islamic principles. We processed the data using the Partial Least Square-Structural Equation Model (PLS-SEM) method in Smart PLS 4.0 which the data was collected using a self-administrated questionnaire. The results showed that prior experience, moral obligation, self-efficacy, and perceived social support has a significantly positive effect towards the intention of social Islamic entrepreneurial intentions in Indonesian Muslim communities and thus this result can be applied as a reference for policy makers or academics to increasing Islamic entrepreneurial activity and promote Islamic entrepreneurial intentions in society.